The Relationship of Mothers’ Knowledge of Basic Immunization with Babies’ Immunization Status in Toboali Puskesmas of South Bangka Regency - Fabellandari, Vaquita; Hein Intan Wulandari (RSUP Dr Moh Hoesin Palembang, 2022)
Immunization is the process by which a person is immune or resistant to infectious diseases, usually with the vaccine. The aim of research is to find out how the relationship between maternal knowledge about basic immunization with the complete basic immunization in infants at Toboali South Bangka Regency Health Center. This research was conducted with cross sectional analytic method. The population in this study were 73 respondents, who were in accordance with the inclusion and exclusion criteria that have been established by researchers. Distribution rate of mothers knowledge of basic immunization in Puskesmas Toboali South Bangka Regency, with a yield of 47.95% had less knowledge of good and amounted to 52.05% of respondents had good knowledge. Mother's attitudes unfavorable category amounted to 41.09%, both categories amounted to 58.91% and the mother acts unfavorable category by 53% while both categories by 47%. The results of the study with square chi showed significant association between maternal knowledge about basic immunization with complete basic immunization is based on statistical analysis chi square correlation with the value x2 = 9.272 with significant value that can be accepted where the value of p = 0.002 ( α) of 0.05 (p < 0.05).To the health officer on duty in the village of Toboali is expected to continue immunization activities by running Posyandu activities on a monthly basis, and remain members the latest information about immunization.